2014
DOI: 10.1177/1470320313503692
|View full text |Cite
|
Sign up to set email alerts
|

Lack of RAAS inhibition by high-salt intake is associated with arterial stiffness in hypertensive patients

Abstract: Hypothesis/introduction:The relationship between salt intake, blood pressure and RAAS activation is still controversial, being that both high-and low-salt intakes are associated with cardiovascular events in a J-shaped curve pattern. We hypothesized that different patterns of RAAS response to dietary salt intake among hypertensives could be identified, while vascular damage would be related to high-salt intake plus absence of expected RAAS inhibition. Objective: We aim to assess the relationship between sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The biological behaviors of smooth muscle cells above-mentioned are triggered by the activated renin-angiotensin system and reactive oxygen species. [ 30 32 ] Secondly, studies have also indicated that the essential role of UA in arterial stiffness before the development of hypertension may be attributed to the activation of inflammatory pathways (increased levels of C-reactive protein and other proinflammatory factors). [ 33 ] Thirdly, UA has also been implicated in endothelial cell dysfunction, which plays a crucial role in arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…The biological behaviors of smooth muscle cells above-mentioned are triggered by the activated renin-angiotensin system and reactive oxygen species. [ 30 32 ] Secondly, studies have also indicated that the essential role of UA in arterial stiffness before the development of hypertension may be attributed to the activation of inflammatory pathways (increased levels of C-reactive protein and other proinflammatory factors). [ 33 ] Thirdly, UA has also been implicated in endothelial cell dysfunction, which plays a crucial role in arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…In a single study, Kotliar et al indicate a significant positive association between Na and PWV only in the group of participants who had high RAAS activity. However, the group with high Na and low RAAS activity did not show a significant association with PWV [24]. One of the studies suggested that only middle-aged and not young participants presented increased PWV after a high-salt diet [43].…”
Section: Na and Arteriosclerosismentioning
confidence: 95%
“…Moreover, one out of the 11 studies showed that high Na excretion (mean: 2898 mg/day, range 2035.5-3588) is associated with cfPWV only when high Na excretion was combined with high renin-angiotensin-aldosterone system (RAAS) activity but not in the other groups (i.e., those with high Na and low RAAS, low Na and low RAAS, as well as low Na and high RAAS) [24].…”
Section: Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Other studies have demonstrated that a pro-thrombotic state can be induced by the activation of the renin-angiotensin system (RAS), which is associated with arterial stiffness in hypertensive patients. 31,32 Remková et al reported that hypertensive patients have a significant increase in sEPCR levels versus the healthy controls. The sEPCR level decreases in response to the treatment with an angiotensin II type 1 receptor blocker (ARB).…”
Section: Discussionmentioning
confidence: 99%